Impact of Artificial Intelligence in TVET and STEM Education among Higher Learning Students in Malaysia - Mohammad Aniq Bin Amdan; Naldo Janius; Mohd Safwan Bin Saidin; Mohamad Aidil Hazidi Bin Kasdiah (Scientia Publica Media, 2025)
The advancement of Technologies such as Artificial Intelligence (AI) tools are widely used and help in education such as in Technical and Vocational Education and Training (TVET), as well as Science, Technology, Engineering and Mathematics (STEM). This qualitative study is to identify the impact of AI on students in higher learning settings of TVET and STEM programs in Malaysia. From among science and engineering students, this study aimed to identify in what ways the tools and technologies impact on these learners’ experiences, impact their learning, their academic performance, and preparedness for their careers in the future. This study uses a thematic analysis research design. The sample will consist of 10 participants selected based on varying experiences and views. The research method chosen is an in-depth interview, meaning that it will go into details about the benefits and challenges of AI use in education as they are perceived by students. The initial findings will provide an insight into crucial themes enhancement in learning efficiency, development of critical thinking skills, and challenges resulting from the adoption of new technologies. In addition, this research also identifies possible application areas of AI for improving educational outcomes in TVET and STEM and possible barriers for effective implementation. Findings will provide an overview of the knowledge base at the present time about the adoption of AI in the higher learning sector, with associated meaning for educators, and institutions that are considering embedding AI into curricula. The outcome will further realize how AI could be applied to narrow the gap between traditional ways of educating people regarding the demands of an increasingly digitalized workforce, hence significantly improving the employability of TVET and STEM graduates in Malaysia.